Analisis Pengaruh Store Atmosphere, Product Quality, dan Price Discount terhadap Loyalitas Pelanggan pada Matahari Department Store Melalui Kepuasan Konsumen sebagai Variabel Intervening - Suhartono, Suhartono; Prianti, Hanna Frisda (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study aims to determine the effect of store atmosphere, product quality and price discount on customer loyalty at Matahari Depatment Store through consumer satisfaction as an intervening variable (case study at Matahari Department Store branch Pakuwon Mall Yogyakarta). The population of this research is visitors Matahari Department Store branch Pakuwon Mall Yogyakarta with a sample of 130 responden. This study uses a quantitative descriptive method using primary data obtained from distributing questionnaires. In this study using proposive sampling techniques. The result of this study show that store atmosphere does not have a direct positive effect customer loyalty, product quality has a positive effect customer loyalty, price discount has a positive effect customer loyalty, consumer satisfaction has a positive effect customer loyalty, store atmosphere has a positive effect consumer satisfaction, product quality has a positive effect consumer satisfaction, price discount has positive effect consumer satisfaction, and store atmosphere, product quality, and price discount are able to mediate consumer satisfaction on customer loyalty.